الشیخ أحمد رضا خان القادري رحمه الله وحاشیته جد الممتار علی رد المحتار - Manzoor Ahmad; Hafiz Abdul Majeed (Pakistan Journal of Islamic Research)
Maulana Ahmad Raza Khan was an august scholar of the sub-continent. He was bestowed with ingenuity and competence in different branches of Islamic studies. The same characteristics led him to make a considerable contribution in Islamic jurisprudence. His exhaustive work entitled 'Fatawa Rizvia' provides an ample proof of his literary, creative and juristic expertise, winning for him a distinct place in the whole sub-continent. Such another evidence comes from his marginal notes named 'Jad al Mumtar' on a renowned book of Hanafi school of thought 'Rad al Muhtar'. This is a short commentary published in seven volumes, which shows Imam Ahmad Raza Khan's high sagacity, eloquence and rhetorical expertise. Here, he comes up with a quite just analysis on Rad al Muhtar, indicating literal, implied and historical inaccuracies if found therein. The commentator has such an extensive study on the subject that he gives a lot of references for elucidation of a particular word or point and, when differs, presents his preferential opinion with cogent arguments. Jad al Mumtar is, no doubt, a precious gift not only for the jurists and research scholars but also for general readers having interest in the field.